2018
DOI: 10.1039/c7np00042a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and stereochemical diversity in prenylated indole alkaloids containing the bicyclo[2.2.2]diazaoctane ring system from marine and terrestrial fungi

Abstract: Various fungi of the genera Aspergillus, Penicillium, and Malbranchea produce prenylated indole alkaloids possessing a bicyclo[2.2.2]diazaoctane ring system. After the discovery of distinct enantiomers of the natural alkaloids stephacidin A and notoamide B, from A. protuberus MF297-2 and A. amoenus NRRL 35660, another fungi, A. taichungensis, was found to produce their diastereomers, 6-epi-stephacidin A and versicolamide B, as major metabolites. Distinct enantiomers of stephacidin A and 6-epi-stephacidin A may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 140 publications
1
71
0
Order By: Relevance
“…Data on soil isolation of Aspergillus niger ( Chaıneau et al, 1999 ) , Aspergillus fumigatus ( Chaıneau et al, 1999 ; Zafra et al, 2014 ), Aspergillus terreus ( Da Silva et al, 2003 ), Aspergillus flavus, Aspergillus niger, Aspergillus nomius ( Zafra et al, 2014 ), Aspergillus sydowii ( Tian et al, 2016 ), Aspergillus versicolor ( Šimonovièová et al, 2017 ) have been reported although few information deals with the here-detected species of Aspergillus (i.e., A. creber, A. jensenii, A. protuberus ). For instance, A. creber and A. jensenii , described as new species in Jurjevic et al (2012) , are mostly known as air-born contaminants or of clinical relevance ( Micheluz et al, 2016 ; Siqueira et al, 2016 ); A. protuberus has been isolated from air and the mussel Mytilus edulis galloprovincialis ( Siqueira et al, 2016 ; Klas et al, 2018 ). There is no evidence in literature of these species as a terrestrial inhabitant.…”
Section: Discussionmentioning
confidence: 99%
“…Data on soil isolation of Aspergillus niger ( Chaıneau et al, 1999 ) , Aspergillus fumigatus ( Chaıneau et al, 1999 ; Zafra et al, 2014 ), Aspergillus terreus ( Da Silva et al, 2003 ), Aspergillus flavus, Aspergillus niger, Aspergillus nomius ( Zafra et al, 2014 ), Aspergillus sydowii ( Tian et al, 2016 ), Aspergillus versicolor ( Šimonovièová et al, 2017 ) have been reported although few information deals with the here-detected species of Aspergillus (i.e., A. creber, A. jensenii, A. protuberus ). For instance, A. creber and A. jensenii , described as new species in Jurjevic et al (2012) , are mostly known as air-born contaminants or of clinical relevance ( Micheluz et al, 2016 ; Siqueira et al, 2016 ); A. protuberus has been isolated from air and the mussel Mytilus edulis galloprovincialis ( Siqueira et al, 2016 ; Klas et al, 2018 ). There is no evidence in literature of these species as a terrestrial inhabitant.…”
Section: Discussionmentioning
confidence: 99%
“…13) [19]. AuaJ is proposed to perform an epoxidation that is followed by AuaI-catalyzed hydrolysis to form aurachin A (66), which functions similarly to the pyran and dioxepin ring-forming enzymes within fungal indole alkaloid biosynthesis [19]. In this case, two enzymes (AuaG and AuaH) perform the proposed function of PhqK and NotI in paraherquamide and notoamide biosynthesis, respectively.…”
Section: Mechanism Of Pyran and Dioxepin Ring Formationmentioning
confidence: 99%
“…Among these natural products are a series of reverse-prenylated indole alkaloids that exhibit a wide range of bioactivity including, but not limited to, insecticidal, cytotoxic, anthelmintic, and anti-bacterial properties. 1 Representative of this group are the paraherquamides (e.g., 2, Fig. 1), stephacidins (e.g., 5), and marcfortines (e.g., 7), all of which possess a bicyclo[2.2.2]diazaoctane core ring system (highlighted in red in 1).…”
Section: Introductionmentioning
confidence: 99%